Religion according to Gustave Le Bon - Al-Qaragully, Farook; Al-Azzawi, Heba (Al-Adab Journal, 2024)
There is no greater issue that man was invested in in matter of doing, thinking, and speaking since the beginning of time than that of religion. Religion is a common phenomenon that exists everywhere. And it makes a unique human event. It’s known that throughout history there are civilizations without arts, and ones without financial progress, but never a civilization without religion. Within the framework of this unique phenomenon, studies started to search for the roots of the idea of religion in the history of mankind. The French intellectual “Gustave Le Bon” came to unveil the truth about religion. He started to ask plenty of questions such as, how did religion start? What are the primary motives behind the existence of religion? How can a human being believe in a set of unshakable, doctrinal rules? By this research, we will answer all of these inquiries that Gustave Le Bon has presented using the descriptive, analytical method.